2021
DOI: 10.3390/aerospace8030071
|View full text |Cite
|
Sign up to set email alerts
|

Human–Machine Interface Design for Monitoring Safety Risks Associated with Operating Small Unmanned Aircraft Systems in Urban Areas

Abstract: The envisioned introduction of autonomous Small Unmanned Aircraft Systems (sUAS) into low-altitude urban airspace necessitates high levels of system safety. Despite increased system autonomy, humans will most likely remain an essential component in assuring safety. This paper derives, applies, and evaluates a display design concept that aims to support safety risk monitoring of multiple sUAS by a human operator. The concept comprises of five design principles. The core idea of the concept is to limit display c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…These changes in technical skills are likely related to the difference in controls of both systems and should be considered when training skills. From human-machine interaction studies, it is observed that a change in interface requires the operator to switch from a more automated modus, to a more complex neuro control part of the brain that require more active thinking, which may cause problems with execution of the tasks [36][37][38]. The novices and experts experienced less decay of tissue handling skills (MaxForce) when switching from LS to RS, compared to intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in technical skills are likely related to the difference in controls of both systems and should be considered when training skills. From human-machine interaction studies, it is observed that a change in interface requires the operator to switch from a more automated modus, to a more complex neuro control part of the brain that require more active thinking, which may cause problems with execution of the tasks [36][37][38]. The novices and experts experienced less decay of tissue handling skills (MaxForce) when switching from LS to RS, compared to intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…The work mentioned in Ref. [17], highlights that HMI must keep the UAS operator informed at all times about the automation's behavior and its intent. This work focuses on operating multiple UAS by a single operator but in terms of HMI design, it could be applied to single UAS operations.…”
Section: B Remote Pilot Trainingmentioning
confidence: 99%
“…In regard to SPTs and SPIs, they are ultimately linked to the safety risks of an operation. Based on [27], two BowTie 17 diagrams are provided covering the case of MACs and GCs. In these examples, UAS are considered without people on board.…”
Section: Operational Scenariosmentioning
confidence: 99%